Analisis Pengetahuan Masyarakat Tentang Bank Syariah (Studi Kasus Desa Panca Mukti Kecamatan Bagan Sinembah) - A, Adriani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Sharia Bank as an alternative to save funds, for transfers and even for future investments, and one institution that carries out three main functions, namely accepting deposits, lending money, and providing money transfer services. This study aims to answer the formulation of the problem of How is Public Knowledge about Islamic banks in Panca Mukti Village? Which phenomenon is that many people do not know about Islamic banks, let alone use their products. This study The research method used in this study is a qualitative descriptive method, namely research that only collects, compiles, clarifies and interprets data so that it can provide a clear picture of the problem being studied. The results of this study are that the people of Panca Mukti Village already know about the existence of Islamic banks, but people who know about Islamic banks do not fully know about Islamic banking products. This means that the community already knows about Islamic banks but has not used Islamic banks on the grounds that the Panca Mukti Village Community as public information about Islamic banks at the primary level, especially knowing. The lack of socialization about Islamic banking is one of the causes of ignorance of the Panca Mukti Village community. The existence of conventional banks that have long been used by the people of Panca Mukti Village also triggers the cause of some people not being interested in making transactions at Islamic banks and the products available in Islamic banks.